IMPLEMENTATION OF EMKM FINANCIAL ACCOUNTING STANDARDS IN PREPARING FINANCIAL STATEMENTS AT FAMILY STORES - Simamora, Khairisa Putri; Wardayani, Wardayani (Jurnal Ekonomi, 2023)
This research was conducted on the Toko Family business which is one of the MSMEs in Jl. Mulya Dusun III Buntu Desa Sidodadi. Kec. Biru-biru Kab. Deli Serdang. The purpose of this study is to determine the application of SAK EMKM financial statement preparation in family stores. The research methods chosen were qualitatively descriptive. According to the findings, this family store does not keep detailed records, only records expenses and income, and has no records such as income statement and balance sheet, so financial statements according to SAK EMKM not using Notes on financial statements. According to SAK EMKM, these are currently the contents of the annual financial statements that MSMEs must prepare.